2014
DOI: 10.1177/0300985814549951
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Angiogenic Factors by Neoplastic Epithelial Cells Is Associated With Canine Prostatic Carcinogenesis

Abstract: The dog is the only species, other than humans, in which spontaneous prostatic cancer occurs; therefore, dogs are a valuable model for the study of factors that regulate tumor progression. Angiogenesis is important in the development and spread of a variety of cancers, including prostate cancer. To better define the role of cancer epithelial cells in prostate cancer neovascularization, immunohistochemical staining for angiogenic factors (vascular endothelial growth factor [VEGF], platelet endothelial cell adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
(60 reference statements)
1
9
0
Order By: Relevance
“…35 In the present study, VEGF, VEGFR1 and VEGFR2 were presented in epithelial and stromal cells during both the breeding and non-breeding seasons, which suggested that the prostate of the wild male ground squirrels potentially possessed the ability to synthesize VEGF and its receptors, and it was concluded that VEGF might affect the physiological functions of the prostate. Similar results also were observed in other breeding mammals, including human, 36 mice 37 and dogs, 38 which showed that VEGF and its receptors regulated a series of physiological responses, such as proliferation and migration of prostatic endothelial cells and vascular permeability, in the form of paracrine or autocrine. Our previous studies showed that COX-1, COX-2, prostaglandin E synthase (PTGES) and prostaglandins E2 receptors (PTGERs) were expressed in the epithelial and stromal cells of the prostate during the breeding and non-breeding seasons, thus suggesting that PGE2 synthesis and signaling might play an important autocrine or paracrine role in the regulation of seasonal changes in the prostatic function of the wild ground squirrels.…”
Section: Discussionsupporting
confidence: 83%
“…35 In the present study, VEGF, VEGFR1 and VEGFR2 were presented in epithelial and stromal cells during both the breeding and non-breeding seasons, which suggested that the prostate of the wild male ground squirrels potentially possessed the ability to synthesize VEGF and its receptors, and it was concluded that VEGF might affect the physiological functions of the prostate. Similar results also were observed in other breeding mammals, including human, 36 mice 37 and dogs, 38 which showed that VEGF and its receptors regulated a series of physiological responses, such as proliferation and migration of prostatic endothelial cells and vascular permeability, in the form of paracrine or autocrine. Our previous studies showed that COX-1, COX-2, prostaglandin E synthase (PTGES) and prostaglandins E2 receptors (PTGERs) were expressed in the epithelial and stromal cells of the prostate during the breeding and non-breeding seasons, thus suggesting that PGE2 synthesis and signaling might play an important autocrine or paracrine role in the regulation of seasonal changes in the prostatic function of the wild ground squirrels.…”
Section: Discussionsupporting
confidence: 83%
“…Expression of angiogenic factors such as vascular endothelial growth factor has been detected in dogs with PC . While numbers in this study were too small and combination therapy with NSAIDs was used, drugs targeting these receptors may be a strategy for therapy in future research . Other potential targets could be the BRAF V595E mutation .…”
Section: Discussionmentioning
confidence: 97%
“…43 While numbers in this study were too small and combination therapy with NSAIDs was used, drugs targeting these receptors may be a strategy for therapy in future research. 44 Other potential targets could be the BRAF V595E mutation. 18 Ten more dogs treated with metronomic chemotherapy plus NSAIDs were assessed together with those patients receiving toceranib phosphate as a separate group and compared to dogs treated with NSAIDs alone.…”
Section: Discussionmentioning
confidence: 99%
“…Most LPs examined were characterized by high FGF2 expression, chiefly in well-differentiated and pleomorphic LP histotypes. FGF2 expression has been reported in several canine neoplasms, including epithelial tumors such as prostatic carcinoma, 41 endocrine and thyroid carcinoma, 43 and mesenchymal neoplasms such as hemangiosarcoma 55 and fibrosarcoma. 14 FGF2 expression has also been investigated in human STS where FGF2 plasma levels were higher than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%